Assessing Measurement Invariance of the Student Personal Perception of Classroom Climate Across Different Ethnic Groups. (August 2016) - Rubie-Davies, Christine; Asil, Mustafa; Teo, Timothy
The class climate is acknowledged as being related to student learning. Students learn more in classrooms that are supportive and caring. However, there are few class climate instruments at the elementary school level. The aim of the current study was to assess the measurement invariance of a recently developed scale in a different context (New Zealand) from where it was developed (the United States) and across different ethnic groups. A total of 1, 924 elementary school students (963 males and 961 females) participated. Students completed the Student Personal Perception of Classroom Climate (SPPCC). Results of the invariance tests of the SPPCC across four ethnic samples (New Zealand European, Māori, Pasifika, and Asian) indicated that the SPPCC represented the same four factors in classroom climate for each of these groups (configural invariance). Results also revealed that full metric invariance was supported although only partial scalar invariance was achieved because of a lack of invariance in the thresholds for five items. Therefore, this study provided empirical support for the SPPCC when used within a new context and with different ethnic groups. Future studies to enhance the usability of the SPPCC are discussed.